2018
DOI: 10.3390/separations5040047
|View full text |Cite
|
Sign up to set email alerts
|

Fixed- and Variable-Temperature Kinetic Models to Predict Evaporation of Petroleum Distillates for Fire Debris Applications

Abstract: Forensic fire debris analysis focuses on the identification of a foreign ignitable liquid in debris collected from the scene of a suspected intentional fire. Chromatograms of the extracted debris are compared to a suitable reference collection containing chromatograms of unevaporated and evaporated ignitable liquids. However, there is no standardized method for the evaporation of ignitable liquids and the process itself can be time consuming, which limits the number of chromatograms of evaporated liquids inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The intensity will be adjusted depending on the degradation of the specific type of oil. According to McIlroy et al (2018) and Butler (1976), the fraction of the original diesel compound remaining after evaporation can be adjusted to a kinematic law:…”
Section: The Transport Problemmentioning
confidence: 99%
“…The intensity will be adjusted depending on the degradation of the specific type of oil. According to McIlroy et al (2018) and Butler (1976), the fraction of the original diesel compound remaining after evaporation can be adjusted to a kinematic law:…”
Section: The Transport Problemmentioning
confidence: 99%
“…k 1 only quantifies the dynamics of the process under the specific measuring conditions (temperature, pressure, or gas–liquid interfacial fluxional area). Other authors have previously reported first-order phenomenology for the late evaporation stage of liquid mixtures. , …”
Section: Introductionmentioning
confidence: 98%
“…Other authors have previously reported first-order phenomenology for the late evaporation stage of liquid mixtures. [9][10][11][12]14 We report here results on the initial zero-order kinetic phase since the present study aims to answer the question whether r evap (initial) is an accurate descriptor of the volatility of liquid mixtures in place of r evap (AcOBu = 1) values commonly missing in SDS. A qualitative interpretation of the rate data is offered for the 15 mixtures included in this study.…”
Section: Introductionmentioning
confidence: 99%
“…When the casework sample is partially evaporated, it becomes necessary to prepare a comparable reference sample. McIlroy and coworkers address the need to prepare accurately evaporated samples by numerically estimating the chromatographic profile of a partially evaporated ignitable liquid for comparison with the residue contribution of a casework sample [6].…”
mentioning
confidence: 99%